Prevalence, Trends, and Projections of Overweight and Obesity Among Children and Adolescents in Indonesia, 1993–2050: A Meta-Analysis of Observational Studies - Azza Fithra Alhanifa; Tresna Ananda Dewi Purbasari; Putu Cintya Denny Yuliyatni (Majalah Kesehatan Indonesia, 2026)
Overweight and obesity among children and adolescents are growing public-health challenges with long-term consequences for noncommunicable disease burden. This study primarily aimed to estimate the pooled prevalence of overweight and obesity among Indonesian school-aged children and adolescents; secondarily, we examined temporal trends and estimated number of cases through 2050. We conducted a meta-analysis of cross-sectional studies up to 10 September 2025. Pooled estimates used random-effects models with heterogeneity assessed by I2. Publication bias was explored and adjusted using trim-and-fill when indicated. Subgroup analyses included sex, school level, and period. Temporal trends were modelled with Autoregressive Integrated Moving Average (ARIMA) and projected to 2050 using national demographic data. A total of 152 studies were included. The pooled prevalence of combined overweight and obesity was 18.13% (95% CI: 15.02–21.71%); obesity alone 7.49% (95% CI: 5.89–9.47%); overweight alone 11% (95% CI: 10–13%). Substantial between-study heterogeneity (I2 = 77.5–99.9%) was observed. Higher prevalence was found in boys and primary-school children. ARIMA projections indicate an increase in combined prevalence to 23.02% by 2050. About one in five Indonesian children and adolescents are affected by overweight or obesity with projected increases, highlighting the urgent need for targeted, multisectoral prevention strategies, especially at primary-school age, to curb future noncommunicable-disease burden. However, given the high between-study heterogeneity consistently observed across all categories, these estimates and projections should be interpreted cautiously as indicative rather than definitive figures.